REFORMING ENVIRONMENTAL GOVERNANCE IN RESPONSE TO INDONESIA’S NICKEL INDUSTRIAL POLICY: A CRITICAL ASSESSMENT OF SUSTAINABILITY CHALLENGES - Rosada, Farah (UI Scholars Hub, 2025)
This study evaluates the effectiveness of Indonesia’s environmental policy reforms in the nickel sector as a response to global criticism regarding ecocidal practices. Indonesia's nickel industry plays a crucial role in the global supply chain, especially in meeting the demand for electric vehicles. However, the ecological impacts of this industry have drawn international scrutiny, particularly from environmental organisations highlighting extensive ecosystem damage. Using environmental security theory, this study focuses on evaluating policy reforms, such as the revision of Environmental Impact Assessments (AMDAL) and the regulation of hazardous and toxic waste (B3), as well as their impacts on ecosystem sustainability and social stability. The findings indicate that policy reforms tend to be reactive and face substantial implementation challenges in the field, which limits their effectiveness in reducing environmental degradation. Additionally, this research contributes to the environmental governance literature by highlighting the discrepancy between policy and practice, particularly in developing countries that face significant challenges in meeting global sustainability standards. The results of this study suggest that Indonesia requires a stronger and more sustainable governance approach to address global sustainability demands.